From Errors to Engagement: Gamification and Digital Tools in Teaching English Pronunciation to Arabic Speakers: - Rama Mohamed Kamal Ahmad Rustom; Alzahraa Mandour Sayed (Journal of English Language Teaching and Applied Linguistics, 2025)
Background of the Study: This study investigates the phonological errors in English pronunciation made by Egyptian university students whose first language is Arabic (L1). These errors are shaped by both first language interference and internal L2 challenges. Aims and Scope of the Paper: The research categorizes errors into interlingual and intralingual types and emphasizes pedagogical strategies tailored to these challenges, with a specific focus on gamification and technology enhanced learning. Methods: Data were collected through classroom observations and recorded speech samples from English language lectures. The recordings were transcribed and analyzed. Interlingual errors included vowel length confusion, consonant substitution, and cluster reduction, while intralingual errors involved overgeneralization and incorrect stress placement. Result: The findings provided authentic insight into learners' spoken interactions. Phonological patterns influenced by Arabic L1 and internal misapplication of English phonological rules were clearly identified and analyzed. Gamified strategies were proposed as targeted interventions. Conclusion: This study highlights the importance of integrating creative digital tools such as pronunciation based apps, rhythm based games, and role-play tasks into pronunciation instruction. These tools help transform error correction into a more dynamic and learner centered experience. The study contributes a practical model for improving phonological competence among Arabic-speaking EFL learners through innovative, evidence-based pedagogy.